2011
DOI: 10.1673/031.011.14301
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Distinctly Marking Honey Bees,Apis mellifera, Originating from Multiple Apiary Locations

Abstract: Inexpensive and non-intrusive marking methods are essential to track natural behavior of insects for biological experiments. An inexpensive, easy to construct, and easy to install bee marking device is described in this paper. The device is mounted at the entrance of a standard honey bee Apis mellifera L. (Hymenoptera: Apidae) hive and is fitted with a removable tube that dispenses a powdered marker. Marking devices were installed on 80 honey bee colonies distributed in nine separate apiaries. Each device held… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 23 publications
(39 reference statements)
0
24
0
2
Order By: Relevance
“…Esto es particularmente relevante en ambientes en donde la humedad relativa es elevada y provoca la aglomeración rápida de polvos, imposibilitando su paso a través de los poros de la tela dispensadora. Por el tipo de materiales usados, el dispositivo que se presenta en este manuscrito es más económico y de más fácil construcción que los desarrollados por otros autores (Hagler et al 2011, Martin et al 2006, Vélez 2005. Además que demostramos que las sustancias que usamos para marcar no afectaron significativamente la conducta ni la supervivencia de las abejas marcadas, aspecto esencial que se tiene que comprobar para asegurar que los datos obtenidos estén libres de sesgo.…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…Esto es particularmente relevante en ambientes en donde la humedad relativa es elevada y provoca la aglomeración rápida de polvos, imposibilitando su paso a través de los poros de la tela dispensadora. Por el tipo de materiales usados, el dispositivo que se presenta en este manuscrito es más económico y de más fácil construcción que los desarrollados por otros autores (Hagler et al 2011, Martin et al 2006, Vélez 2005. Además que demostramos que las sustancias que usamos para marcar no afectaron significativamente la conducta ni la supervivencia de las abejas marcadas, aspecto esencial que se tiene que comprobar para asegurar que los datos obtenidos estén libres de sesgo.…”
Section: Resultados Y Discusiónunclassified
“…El marcaje individual se basa en la aplicación de etiquetas numeradas o de pinturas que permitan la identificación de un individuo específico dentro de un grupo (Vélez 2005), como en estudios conductuales realizados con la abeja Scaptotrigona mexicana (Sán-chez & Vandame 2012). El marcaje masivo consiste en el uso de polvos y/o pinturas aplicadas simultáneamente a un grupo de insectos, por lo que no es posible distinguirlos individualmente (Hagler et al 2011), como en estudios de captura y recaptura con mosquitos (Ciota et al 2012). En este manuscrito describimos un dispositivo usado con éxito para el marcaje masivo de abejas Apis mellifera Linnaeus, 1758 (Hymenoptera: Apidae) que se fija fácilmente a la piquera de una colmena comercial y que marca el tórax con pintura líquida, a diferencia de los dispositivos de marcaje masivo descritos hasta ahora que se basan en la aplicación de polvos fluorescentes.…”
unclassified
“…Although fluorescent marking system has been employed when monitoring multiple insect species, Rice et al . were the first to evaluate and demonstrate the potential of a handheld laser in detection of fluorescent‐marked insects from a long distance . Nevertheless, although the results by Rice et al .…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescent marking has been used to observe and study the behavior and dispersal of a large number of insects such as mosquitoes and bees because it is easy to access and apply to large groups of insects . Traditional pairing of fluorescent marking with ultraviolet (UV) lamps is labor‐intensive and inefficient when target animals have high mobility due to its short range of illumination .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Hagler et al 8,27 showed that honey bees can self-mark with egg white and bovine milk dry powders as they exit through a protein dispenser placed at the entrance of a hive ( Figure 3D). Perhaps the most creative use of the protein marking involved targeting cow pats with egg whites using a jet sprayer 28 .…”
Section: Introductionmentioning
confidence: 99%